Risk Factors Associated With Early-Onset Colorectal Neoplasm in Chinese Youth: A Prospective Population-Based Study - Shen, Jie; Wu, Yiling; Mo, Miao; Feng, Xiaoshuang; Zhou, Changming; Wang, Zezhou; Cai, Guoxiang; Zheng, Ying (Frontiers in Oncology, 2021)
Evidence of the risk factors associated with early-onset colorectal neoplasm from prospective population-based studies is limited. We enrolled 17,293 participants younger than 50 years from the Shanghai colorectal cancer (CRC) screening program cohort. Face-to-face interviews were performed by trained primary care physicians using a standardized questionnaire to collect the information on potential risk factors at baseline entry. Furthermore, 124 cases of early-onset colorectal neoplasm, including six CRC cases and 118 colorectal adenoma (CRA) cases, were detected between 2012 and 2016. Multivariable logistic regression models and restricted cubic spline (RCS) were used to evaluate the risk factors associated with early-onset colorectal neoplasm. We found that sex, body mass index (BMI), and family history of CRC were associated with the early onset of colorectal neoplasm. The RCS model showed a positive dose–response and linear association between BMI and risk of early-onset colorectal neoplasm among young participants (p-overall = 0.19, p-nonlinear = 0.97). The findings indicated that it was beneficial for normal people younger than 50 years to start opportunistic CRC screening. As for those at high risk, increased surveillance is strongly recommended. Further close follow-up is required for research on the underlying causes of early-onset CRC.